Benefits of prehabilitative exercise on physiological, functional and patient-reported outcomes in patients undergoing oncologic surgery: A systematic review and meta-analysis - Natália Casagrande; Favil Singh; Anderson Rech; Régis Radaelli; Bruna M. Paniz; Guilherme T. Silvestro; Guilherme N. Eberhardt; Janaína Brollo; Maximiliano C. Kneubil; Claudio P. Júnior; Pedro W. M. de Almeida; Maria Cristina F. Magalhães; et al. (Journal of Cancer Survivorship, 2026)
Abstract Purpose Prehabilitation, delivered between cancer diagnosis and surgery, may enhance functional reserve and improve tolerance to surgical stress, but evidence remains conflicting across cancer types and outcomes. We aimed to evaluate the effects of prehabilitative exercise on physiological, functional, and patient-reported outcomes in patients undergoing oncologic surgery. Methods A systematic review and meta-analysis was conducted (PROSPERO: CRD420251072796). Randomized controlled trials comparing structured exercise interventions with usual care in adults undergoing oncologic surgery were included. Searches were performed across seven databases until June 2025. Outcomes included cardiorespiratory fitness, muscle strength, physical function, fatigue, psychological distress, and quality of life. A three-level mixed-effects meta-analysis evaluated intervention effects and moderators. Results Twenty-seven studies ( n = 2005) were included. Prehabilitation significantly improved cardiorespiratory fitness (SMD 0.31, p = 0.010), physical function (SMD 0.36, p < 0.001), and quality of life (SMD 0.19, p = 0.030), with sustained postoperative benefits in physical function. Fatigue was reduced preoperatively (SMD –0.21, p = 0.017), while muscle strength and psychological distress were preserved relative to baseline. Certainty of evidence ranged from very low to moderate. Conclusions Prehabilitative exercise improves preoperative fitness, function, fatigue, and quality of life, and attenuates perioperative decline in patients undergoing cancer surgery. These findings support integrating structured exercise into perioperative oncology pathways to optimise recovery and long-term outcomes. Implications for Cancer Survivors Prehabilitative exercise may mitigate perioperative deconditioning and facilitates a return to baseline function. By potentially preserving functional reserve against surgical stress, these interventions could contribute to improved long-term survivorship trajectories and should be considered within structured, individualised perioperative care pathways.